Incorporating Interpersonal Psychotherapy for Postpartum Depression Into Social Work Practice in Israel. (January 2019) - Posmontier, Bobbie; Bina, Rena; Glasser, Saralee; Cinamon, Tali; Styr, Benedict; Sammarco, Therese
Purpose: To determine feasibility and acceptability of incorporating IPT for postpartum depression (PPD) into Israeli social work practice. Method: Women who were 4–24 weeks postpartum with PPD, at least 18 years old, had telephone access, and had a score of 10–18 on the Edinburgh Postnatal Depression Scale (EPDS) were eligible to participate in this two-group, nonrandomized repeated measures pilot. The intervention group received eight 50-min IPT sessions and the comparison group received treatment-as-usual. Primary outcomes were measured with the EPDS, Postpartum Adjustment Questionnaire (PPAQ), and Client Satisfaction Scale-8. Results: There was a significant reduction in both groups in EPDS scores at the end of treatment ( t = −4.68, 95% CI [−6.49, −2.57], d = 1.07) and 4 weeks posttreatment ( t = −5.09, 95% CI [−7.14, −3.08], p < .001, d = 1.21), a significant reduction in PPAQ scores at the end of treatment ( t = −2.09, 95% CI [−0.29, 0.00], p < .05, d = 0.44), and high patient acceptability. Discussion: This study provided preliminary evidence supporting IPT use by social workers in Israel.